HOW CHARACTER BUILDING CAN BE INTEGRATED IN THE TOTAL PHYSICAL RESPONSE (TPR) ON THE SPEAKING ABILITY OF THE BLIND THIRD GRADERS - Irawati, Cindy (English Department of Faculty of Tarbiyah and Teacher Training, 2016)
It was realized that everyone has the right to get the learning especially language. It has no exception for children with special needed, more over for the blind children. On their learning process, it can be sure that the process will be different to the other common children because they must be given special behavior. Although inclusive learning is developed, recently, it still has some lacks on its application. Indonesian rules (UUD?45) guarantee its people to get their right on education and no discrimination for every single human, but there is a special behavior that given to the some cases. On its application, the teachers have to have the ability to reach the goal which is stated on the curriculum, so they must have a skill to develop the content of that curriculum. Basically, the learning of every languages, especially English, has the purpose to make someone has ability to communicate with that language fluently and correctly. For the blind children case, the English learning cannot be taught with common model but it must be given with suitable model in order to make learning process effectively. This is a descriptive bibliography method. The writer tries to differentiate between references in some books and articles which are written by the experts and also add some ideas here. The purpose of this research is to find some sub topics which have connection to children with special need, the learning model of TPR and also the application of TPR model on speaking learning for blind children in order to get application of character building on self confidence and learning successfully.